Estimation Of Trace Amounts Of Chromium (III) In Various Multi-Vitamin Pharmaceutical Formulations - NISHA.H.PARIKH; RAJASHREE C.MASHRU (International Journal of Pharma and Bio Sciences, 2010)
New specific, selective, simple & inexpensive spectroscopic method for estimating a trace amount of chromium (Cr+3) from pharmaceutical formations was developed. The proposed method is based on the conversion of Cr+3 to Cr+6 by oxidation with a sodium hydroxide-hydrogen peroxide followed by the complexation of Cr+6 with 1.5 diphenylcarbazide (DPC) in a mineral acidic solution of pH 1.0±0.5. The pink-colored complex was estimated at 540 nm.The advantage of method is that it does not required preashing of the sample as it shown in the various method. Method was found to be linear in the range of 1-9 µg/ml. with a limit of detection is 0.166µg/ml and a limit of quantitation is 0.555 µg/ml. Method was found to be suitable for estimating Cr+3 species in various formulations. Satisfactory recovery from spiked samples of standard Cr+3 suggests no interference of any excipiants and diverse ions present in a formulation.